Management of accidental exposure to HCV, HBV and HIV in healthcare workers in Romania - Malka, Eyal (National Institute of Infectious Diseases “Prof. Dr. Matei Balş”, Romania, and the European Academy of HIV/AIDS and Infectious Diseases, 2012)
INTRODUCTION: Accidental blood exposure in healthcare workers is an important issue worldwide. We present a study which analyzed the route of exposure, the source of infection and the post-exposure prophylaxis treatment administered. METHOD: We performed retrospective study of occupational exposure to HBV, HCV and HIV and the subsequent post-exposure prophylaxis among healthcare workers at the National Institute of Infectious Diseases “Prof.Dr. Matei Balş”, Bucharest, Romania, from December 2002 to December 2011. RESULTS: Sixty healthcare workers with a mean age of 36 reported an occupational exposure during a period of 9 years, 54 (90%) were females and 6 (10%) were males. 48 (80%) exposed healthcare workers were nurses, 7 (11.6%) were doctors and 5 (8.3%) were medical assisting staff. In 49 (81.6%) cases the exposure was percutaneous and in 11 (18.3%) cases the exposure was mucosal/corneal. Ten (16.6%) exposed healthcare workers had insufficient levels of antibody (HBsAb) response, (below 10 mIU/mL), 6 (10%) had titers between 11 and 500 mIU/mL, 31 (51.6%) between 501-1000 mIU/mL, and 13 (21.6%) above 1000 mIU/mL). DISCUSSION: The exposure events analysis in this study yielded similar results compared to other previous parallel studies. Minimizing risks to HCWs for acquisition of blood-borne pathogens and correct and rapid post-exposure prophylaxis treatment in case of exposure should be an integral part of the infection control and occupational health programs in all healthcare facilities.